Patient safety culture in Dentistry: An integrative literature review (Research, Society and Development, 2023)
Patient safety culture promotes the implementation of safe practices and the reduction of adverse events during healthcare delivery. Organizations with positive safety cultures are characterized by communication and trust, a shared perception of the concept of patient safety, and the effectiveness of preventive measures. There is limited research on patient safety culture and Dentistry, whether in isolated healthcare settings or in relation to professional training. This integrative literature review aims to identify and analyze the evidence regarding patient safety culture in Dentistry. The research sources were obtained through a bibliographic search, using articles published in the PUBMED database. The results show studies that employed different instruments, many of which were adapted for assessing patient safety culture in Dentistry. It is evident that the perception of the patient safety culture in Dentistry varies significantly and is influenced by the location, type and length of the professional’s practice, as well as working conditions. Positive attitudes are particularly associated with support for patient safety management and teamwork. The assessment of the patient safety culture in the various practice settings of dental professionals should be encouraged, as it allows for the recognition of strengths and weaknesses that will guide actions for improving healthcare delivery.